Black Panther. Vol. 1, The long shadow - Ridley, John, 1965- (Marvel Worldwide, Inc., 2022)
Secrets from the Panther's past have come back to haunt him. Fresh from returning from his travels in space, T'Challa receives an unexpected and urgent message from a Wakandan secret agent. Now the Black Panther must race the clock not only to save his agent, but also to keep his true agenda under wraps. Because if the truth comes out, it could cost T'Challa everything ...